If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6 + 4k) = -18 + 8k (6 * 7 + 4k * 7) = -18 + 8k (42 + 28k) = -18 + 8k Solving 42 + 28k = -18 + 8k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-8k' to each side of the equation. 42 + 28k + -8k = -18 + 8k + -8k Combine like terms: 28k + -8k = 20k 42 + 20k = -18 + 8k + -8k Combine like terms: 8k + -8k = 0 42 + 20k = -18 + 0 42 + 20k = -18 Add '-42' to each side of the equation. 42 + -42 + 20k = -18 + -42 Combine like terms: 42 + -42 = 0 0 + 20k = -18 + -42 20k = -18 + -42 Combine like terms: -18 + -42 = -60 20k = -60 Divide each side by '20'. k = -3 Simplifying k = -3
| 2w-16+y=180 | | -29+X=-3 | | 15=-9+4w+2w | | 7y=42y+60 | | 21x=176 | | 42-4t=3t | | 3xy-2x=4p-1 | | X^2+8x=2x+40 | | 15=-9+4w+3w | | 3x+11x-20=0 | | 2x+10=5x+25 | | 84=3w | | 17-(3+b)=b | | 8a+15+a^2=0 | | 12x+16=4x+56 | | 5000x^2+60x=0 | | x+3-4x=6x+10 | | X-5=7-x | | 500x^2+6x=0 | | 1+(-3)= | | 3y-2(y-1)=6-(4+1) | | 0=k^2+12k+32 | | -7+4x=6x-5x | | 3x+18=99 | | 11x-y=-15 | | -66=2b-6(6+2b) | | 3x^2-6x-12y+3y^2-12=0 | | 6x+16=-5 | | 2u=38 | | -6x-1+3x=-7x-7 | | 8(y+6)+27=99 | | 16a-8a-8b= |